Control y represión en Zamora (1936-1939). La violencia vengadora ejecutada sobre el terreno - Dios Vicente, LAURA DE (Historia y Comunicación Social, 2002)
Just a day later, the province of Zamora joined the military national rebelion that happened on 18th july 1936, because the military officials knew about the existence of the coup since spring and, as a result, they supported it. Zamora became one of the symbols of the Spain of Franco. Quickly he built that new Spain, first from Burgos and then from Salamanca, by controlling and oppressing every aspect of life. The changes in education, the Falangist control, the Army, the Guardia Civil (spanish police) and the clerical orientation from their churchies and offices, together with a lack of information as well as the poor means of communication, designed a kind of behaviour, the moral and thoughts of the people of Zamora, specially made up of farmers